Tinjauan Pemahaman Masyarakat Terhadap Pidana Politik Uang Pada Pemilu - Trianda Lestari; Syahrando Muhti; Siti Nurhaliza; Dewi Haryanti (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Money politics is a gift or promise to bribe someone so that the person does not exercise their rights in a certain way during the general election. The purchase can be in the form of goods or money, as found by researchers regarding the phenomenon of money politics which is still widespread in three regions, namely , Kijang Bintan, Kawal Bintan, and Lingga, people who are still relatively ignorant and have economic constraints are one of the factors in society being entangled in giving and receiving political money. Apart from damaging democracy due to forms of fraud, this problem has a negative impact on the givers and recipients who have clearly violated the provisions of the election law and violated criminal provisions. However, this problem is still difficult to resolve due to the lack of supervision and firm action. This research uses empirical legal research. This research is a legal research method that uses empirical facts taken from people's behavior, both verbally obtained from interviews and behavior carried out through direct observation. The theory used in this research is not to use critical legal theory, in order to find the problems that occur, as well as reveal how much the public understands money politics. So from these problems it can be drawn with the title Review of Community Understanding of Money Politics